Scleral Necrosis in a Case of Seasonal Hyperacute Panuveitis Successfully Treated with Amniotic Membrane Graft: A Case Report - Shrestha, Eliya; Gurung , Hara Maya; Gurung , Babita; Adhikari, Hari Bikram; Gurung , Krishna; Gurung , Anju (Nepalese Journal of Ophthalmology, 2024)
Introduction: Seasonal hyperacute panuveitis (SHAPU) is still a dilemma in the field of ophthalmology. Every alternate odd year from September until January, children usually present with unilateral painless red eyes if not treated in a timely manner, rapidly progressing to phthisis bulbi. Case: Case was also diagnosed as a case of seasonal hyperacute panuveitis. Observations: However, during the treatment, the patient developed spontaneous scleral necrosis, which has not been reported to date. Conclusion: Seasonal hyperacute panuveitis may have different clinical presentation, therefore cases of seasonal hyperacute panuveitis should be monitored and evaluated properly before initiating treatment.